Pengaruh Pengawasan Dan Efektivitas Kualitas Pelayanan Terhadap Kinerja Karyawan Dokumen Kargo - Kumila Hanik; Andi Sayoto (Majalah Ilmiah Bahari Jogja, 2022)
This studies written to elaborate if there are some influences of supervision and quality service’s efectivity, as free variables, on PT Macoline Indonesia Semarang’s cargo document employees performance, as bound variable. The research method used is a survey method which is then processed with linear regression analysis techniques. This research conducted for three months was done by conducting a survey through questionnaires given to the employees as the samples. The questionnaires given contained questions regarding how significant the influence of supervision and quality service’s efectivity on PT Macoline Indonesia Semarang’s cargo documents employees performance is. The results were inputted into SPSS then shown as tables and graphics to know the influences in a quantitative way. The research method used is a survey method which is then processed with linear regression analysis techniques. The results showed that there is a significant influence of supervision on employee performance, there is a significant influence on the effectiveness of service quality on employee performance and there is a significant influence of supervision and effectiveness of service quality on employee performance of cargo documents.